1991
DOI: 10.1128/jb.173.19.5964-5974.1991
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the ferric enterobactin receptor in gram-negative bacteria

Abstract: Using sodium dodecyl sulfate-polyacrylamide gel electrophoresis of iron-deficient and replete cell

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
87
0
1

Year Published

1992
1992
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(91 citation statements)
references
References 77 publications
3
87
0
1
Order By: Relevance
“…Because it has been previously reported that N. gonorrhoeae can utilize aerobactin (67) and enterobactin (45) as iron sources, we decided to determine if FrpB functioned as either an aerobactin or enterobactin receptor. FA19, FA6808, FA6747, KDF541, KDF541/pABN6, and BN1071 (Table 1) were iron stressed in CDM as described above and plated onto CDM agarose containing 2.5 M 30% iron-saturated Tf.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because it has been previously reported that N. gonorrhoeae can utilize aerobactin (67) and enterobactin (45) as iron sources, we decided to determine if FrpB functioned as either an aerobactin or enterobactin receptor. FA19, FA6808, FA6747, KDF541, KDF541/pABN6, and BN1071 (Table 1) were iron stressed in CDM as described above and plated onto CDM agarose containing 2.5 M 30% iron-saturated Tf.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, it has been reported to utilize the Escherichia coli siderophores aerobactin (67) and enterobactin (45). All gonococci are capable of utilizing Tf-bound iron directly (38).…”
mentioning
confidence: 99%
“…Since surface domains of OM proteins act as receptors for phages and colicins, the variability in their constituent residues may arise from selective pressure to evade such toxic agents and antibodies (4). Indeed, the study of an OM protein, FepA, among various species showed that the surface residues undergo a more rapid evolutionary change than polypeptides that are buried in the OM bilayer (49).…”
Section: Methodsmentioning
confidence: 99%
“…This finding suggests that appropriate natural or synthetic porin peptides may be effective vaccines against enteric bacterial pathogens. However, such evolutionarily preserved regions of OM proteins are known to consist primarily of polypeptides that are buried within the OM bilayer (24,49) and are therefore refractory to immune recognition. The shielding of OM protein epitopes by LPS and capsule further obscures this question (2,9,18,26,32,36,37,56,57).…”
Section: Methodsmentioning
confidence: 99%
“…Together, these receptors enable the meningococcus to use various human iron-loaded proteins, such as lactoferrin, transferrin and haemoglobin [5]. Furthermore, although the meningococcus does not appear to produce its own siderophores, it has the ability to use siderophores secreted by other bacteria [6]. The major iron-limitation-induced OMP of N. meningitidis is a w70-kDa protein designated FrpB (Ferric-repressed protein B) [7].…”
Section: Introductionmentioning
confidence: 99%